2022
DOI: 10.7717/peerj.13488
|View full text |Cite
|
Sign up to set email alerts
|

Association of multiple tumor markers with newly diagnosed gastric cancer patients: a retrospective study

Abstract: Background The purpose of this paper was to explore the correlation between multiple tumor markers and newly diagnosed gastric cancer. Methods We selected 268 newly diagnosed patients with gastric cancer and 209 healthy subjects for correlation research. The detection of multiple tumor markers was based on protein chips and the results were statistically analyzed using SPSS. Results We concluded that gastric cancer was significantly related to gender, age, alpha fetoprotein (AFP), carcinoembryonic antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In many cases, tumor-related biomarkers are also associated with certain tumor pathological parameters 20,21 . When assessing the correlative relationships between PIC, TAT, TM, and t-PAIC levels and tumor stage, vascular invasion, lymph node metastasis, maximum tumor diameter, nerve invasion, and differentiation degree in patients bearing malignant tumors, we had found that TM was positive correlation with vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, tumor-related biomarkers are also associated with certain tumor pathological parameters 20,21 . When assessing the correlative relationships between PIC, TAT, TM, and t-PAIC levels and tumor stage, vascular invasion, lymph node metastasis, maximum tumor diameter, nerve invasion, and differentiation degree in patients bearing malignant tumors, we had found that TM was positive correlation with vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al [ 26 ] found that CEA is an independent prognostic factor in patients with GC, and the establishment of a CNLR prognostic scoring system combined with CEA and neutrophil-lymphocyte ratio can accurately predict the 3-year and 5-year survival rates of patients with GC. It has also been pointed out that the incidence of GC is significantly correlated with gender, age, CEA, alpha-fetoprotein (AFP), CA125, CA199 and CA242 positive levels, and AFP, CEA, CA125, CA199 and CA242 positive levels are significantly higher in M1 GC patients than in M0 patients[ 27 ]. Wang et al [ 28 ] compared the serum CA724 levels between patients with benign gastric lesions and patients with GC, and the results showed that the expression of CA724 in the serum of patients with GC was significantly increased, and the area under the curve of serum CA724 in the diagnosis of GC was 0.849, with high sensitivity and specificity in differentiating GC, which is an important indicator for early screening and auxiliary diagnosis of GC.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin to Fibrinogen Ratio, The hemoglobin, albumin, lymphocyte, and platelet score, multiple tumor markers, increased expression of Histone Deacetylase 5 appear to be useful parameters in predicting orignostic expectancy in gastric tumors. [22][23][24][25] In 2017, the American Joint Committee on Cancer made revisions on cTNM staging system in their 8th Edition. [11] The staging system of American Joint Committee on Cancer only takes the number of positive lymph nodes into consideration but not the positive to total lymph node ratio.…”
Section: Discussionmentioning
confidence: 99%